Peter Sloterdijk, Skum og religion - Hans J. Lundager Jensen (Religionsvidenskabeligt Tidsskrift, 2017)
ENGLISH SUMMARY: Introduction to the work of Peter Sloterdijk, with special attention to his ideas on religion. The article first gives an overview of the main subjects of some of the most important books: Critique of Cynical Reason, the three volumes in the Spheres-trilogy: Bubbles, Globes, and Foams and In the World Interior of Capital. Subsequently, it explains the main topics in the work such as post-enlightenment, immunity systems, anthropology, and theories of social life. Finally, it discusses the main issues in Sloterdijk’s thoughts on religion, based on books such as Rage and Time, and God’s Zeal.